PENDIDIKAN PRANIKAH DALAM PENDEKATAN ISLAM DAN KESEHATAN DI DESA BINAAN CISEENG, KABUPATEN BOGOR - Karimulloh Karimulloh; Afrizal TW; Roni Hidayat; Aya Yahya; Liko Maryudhianto; Raka Radityo; Muhammad Farhan; Hasby Alamsyah; Latanza Wakaramaka (LPPM Universitas Abdurrab, 2025)
Ciseeng Village continues to experience a relatively high divorce rate, indicating the need for premarital education and preparation for couples planning to marry. In response, the community service team from Universitas YARSI implemented a program titled “Premarital Education with an Islamic and Health Approach in the Ciseeng Partner Village” to foster families that are sakinah, mawaddah, and warahmah, while helping reduce divorce rates. The activity involved 20 participants aged 18–28 years, most of whom were youth members of the local mosque. A participatory method was employed through lectures, interactive discussions, and evaluations using a One-Group Pre-Test and Post-Test design. The delivered materials covered self-preparation from an Islamic perspective, concepts of building an Islamic household, and mental health aspects for prospective couples. Data analysis showed a statistically significant difference (p = 0.015), with post-test scores (M = 14.053 out of a maximum score of 20) higher on average than pre-test scores (M = 13.579). Participant evaluations also indicated high satisfaction with the speakers and content. This program underscores the importance of physical and spiritual preparation in establishing harmonious families and contributes to reducing divorce rates.